Visible Light System in Blue Spaces: A Bionic Workrest Model for Ornamentation, Measurement and Communication - San Juan-Urrutia, E; Canete-Arratia, L; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2023)
In the present century, abundant scientific evidence has been produced about the well-being generated by the bodies of water in cities, whether natural or artificial. Making an analogy with green areas, these bodies which can be lagoons, fountains, rivers, ponds and other outdoor water sources, have been denominated as Blue Spaces , showing various positive impacts on mental health and on the incentive to physical activity of the population that access these assets. Today, the operational continuity of these spaces strongly depends on automation and in this context the visible light can contribute through the aesthetic function of Ornamentation, the scanner function of Measurement and the organic function of Communication. However, this automatic system, cause of entropy, it is exposed to the inexorable deterioration of its attitude, which must be recovered. Since it is unknown how these three functions are diminished and then recovered, in this article we propose a model inspired by biological phenomena. This model considers a working stage at night when the attitude of the system decreases as occurs in some animals while they work, and the next stage in the day when the attitude recovers due to the same animals resting. The aim of this bionic model is to contribute to improving the performance of Blue Spaces through the harmonic management of light as a beauty, monitoring and telecommunication agent. © 2023 IEEE.